Ionic Liquid Nafion Nanofiber Mats Composites for High Speed Ionic Polymer Actuators - Akle, B. (2007)
A new attempt is made for application of the NafionTM nanofiber mat prepared by the electrospinning process to solve the main disadvantage of slow response speed of ionomer-ionic liquid transducers. The measured conductivities of water hydrated Nafion electro-spun fibers are 16.8 mS/cm, which are lower than the nominal 110 mS/cm that of H+ Nafion membranes. The uptake is measured to be around 250 wt % compared to 58 wt % obtained in Nafion films. The ionic conductivity of 110 wt % swollen ionic liquids-Nafion mat composite is computed to be 0.9 mS/cm compared to 0.3 mS/cm in ionic liquid-Nafion membrane composite. The speed of response in actuators with an ionic liquid- NafionTM mat is 1.34 %/s compared to 0.88 %/s for that in ionic liquid NafionTM film transducers.